2013
DOI: 10.14798/71.3.660
|View full text |Cite
|
Sign up to set email alerts
|

EVALUATION OF FERMENTED MANGO (Mangifera indica) SEED MEAL IN THE PRACTICAL DIET OF NILE TILAPIA, (Oreochromis niloticus) FINGERLINGS

Abstract: DZȱŘŝȱȱŘŖŗŘ ȱȱȱDZȱŗşȱȱŘŖŗř DZȱśȱ¢ȱŘŖŗř ȱDZȱŗŘȱ¢ȱŘŖŗř ȱ¢ȱȱȱȱȱȱȱǻȱȬ Ǽȱȱȱǻ Ǽȱȱȱ¢ ȱ£ȱȱȱȱ ȱ ȱ ȱ ǰȱ ȱ ȱ ęȱ ǻŚǯŝŜƹŖǯřŘȱ Ǽǯȱ ȱȬȱǻřśƖȱȱǼȱȱ¡¢ȱ ȬȱǻřŚŖŖȱ ȱȦǼȱȱ ȱ¢ ȱ£ȱ ȱ ȱ¢ȱ ȱŖƖȱǻ ŖȦ ȱǼǰȱŘśƖȱǻ ŘśǼǰȱśŖƖȱ ǻ śŖǼǰȱ ŝśƖȱ ǻ ŝśǼȱ ȱ ŗŖŖƖȱ ǻ ŗŖŖǼȱ ȱ ȱ Ȭ ǯȱ ȱ ęȱ ȱ ȱ ȱ ȱ ȱ ȱ śƖȱ ¢ȱ ȱ ȱ ŞŚȱ ¢ǯȱ ȱ ȱȱǻŘǯřŘƖǼȱȱȱȬȬ ȱ ȱ ¢£ȱ ȱ ǰȱ ȱ ¡ȱ ǻŖǯŞŚƖǼȱ ȱ ǯȱ ȱ ȱ ȱ ǻŞǯşŗȱ ȦǼȱ ȱ ȱ ǰȱ ȱ ȱ ȱ ȱǻŖǯŖŗȱȦǼǯȱȱǰȱęȱ ȱȱ ȱȱȱȱ ȱȱǻǁŖǯŖśǼȱȱęȱȱȱ Ŗȱȱ śŖǯȱȱęȱȱȱ Ŗȱȱȱȱȱ Ĝ¢ȱȱǻŗǯŞŞǼǯȱȱ¢ȱȱǻ|ŖǯŖśǼȱȱ ¢ȱ ȱǰȱ ȱ¢ȱ¢ȱȱȱ ȱǯȱȱȱ ȱȱ ȱȱȬ ȱ¢ ȱ£ȱȱśŖƖȱȱ ȱěȱ ǰȱȬ ȱ£ȱȱȱȱ¢ȱȱȱȱȱ ȱęǯ ¢ DZȱ ȱ ȱ¢ ȱ Ȭȱ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 0 publications
11
4
1
Order By: Relevance
“…High-fat content of the fermented MSKM was similar to the range reported by Obasa et al, (2013) andDiarra (2014). While nitrogen-free extract in this study was lower in value than that of Shittu et al, (2013), Obasa et al, (2013), and Dakare et al, (2014. This variation resulted from species difference in the mango seed, processing methods employed, and high moisture content in the fermented MSKM for this study.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…High-fat content of the fermented MSKM was similar to the range reported by Obasa et al, (2013) andDiarra (2014). While nitrogen-free extract in this study was lower in value than that of Shittu et al, (2013), Obasa et al, (2013), and Dakare et al, (2014. This variation resulted from species difference in the mango seed, processing methods employed, and high moisture content in the fermented MSKM for this study.…”
Section: Discussionsupporting
confidence: 88%
“…The nutritional content of fermented MSKM was within the range reported by Shittu et al, (2013) and Diarra (2014) but lower to Obasa et al, (2013). High-fat content of the fermented MSKM was similar to the range reported by Obasa et al, (2013) andDiarra (2014).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The fish fed 50% water lettuce leaf meal along with 50% yellow maize meal was observed to be best among the treatments, with final weight of 84.37 g, 1.24 g daily growth rate, 3.10%/day specific growth rate, 1.00 protein efficiency ratio, 7.49 kg/m 3 total fish yield and 86.67% survival rate. This result agrees with other works of Fasakin et al, 2001 andObasa et al, 2013. These workers reported that at above 50% inclusion levels, growth, feed utilization and digestibility reduced due to the presence of anti-nutritional factors in Azolla Africana leaf meal and fermented mango seed meal respectively.…”
Section: Adedokun Et Al 11(2):028-035 (2017)supporting
confidence: 93%
“…Corn is one of the most commonly used plant-based energetic ingredients in fish diets (Obasa et al, 2013). However, in recent years, the ethanol industry has consumed a large part of produced corn (in the USA it reaches 40%), which can lead to the increase of demand and price of corn for animal and human consumption (Ranum et al, 2014).…”
Section: Introductionmentioning
confidence: 99%